Research on the Two-way Influence of RMB Internationalization Degree and RMB Exchange Rate Fluctuation - Zhuang, Linqin (International Journal of Global Economics and Management, 2025)
Currency is a crucial part of the international payment system, and the international payment proportion of the national currency is an important embodiment of the international status. In this paper, the proportion of RMB international payment is selected to define the degree of RMB internationalization, and the TVP-SV-VAR model is constructed to study the two-way relationship between the degree of RMB internationalization and the RMB exchange rate. The empirical study shows that there is a significant two-way relationship between the degree of RMB internationalization and the RMB exchange rate. The rise of the exchange rate has a more significant positive impact on the degree of RMB internationalization in the short term, and the positive impact of the degree of RMB internationalization on the exchange rate increases with time. Therefore, China should coordinate its exchange rate policy with the process of RMB internationalization and deepen the market-oriented reform of RMB to form a currency anchor. Improving international payment infrastructure and improving the international legal system while exploring new payment technologies; Based on the "Belt and Road" priority to develop regional trade outward extension, enhance geopolitical influence; We will prudently supervise financial markets and promote market opening at a high level.